MEMAHAMI PELUANG TRANSFORMASI RUMAH SAKIT PETROKIMIA GRESIK DARI KELAS C KE KELAS B (Pendekatan Penelitian Kewirausahaan) - Verra Rizki Amelia (ABIS: Accounting and Business Information Systems Journal, 2019)
Abstract This study aims to identify business transformation opportunities of Petrokimia Gresik hospital from C-class to B-class. In this era of JKN, the establishment of hospital classes correlates with the amount of ceiling reimbursement and referrals. The lower the hospital class, the smaller the amount of ceiling, and the number of services recognized by the BPJS is limited to the status of the hospital class. The emergence of the BPJS program makes the determination of hospital class status to be important. Researchers use the entrepreneurial research approach, therefore, the three theories that form the basis of this research are theory of identification and development of opportunities; institutional theory; and the theory of achievement needs. This research is a qualitative research.The author conducts an analysis based on the results of interviews, observation, and documentation analysis. The results of the study show that the opportunity of Petrokimia Gresik hospital has not yet reached business transformation. According to the Getzel matrix, in the theory of identification and development of opportunities, Petrokimia Gresik hospital has the capability of values creation, but has not found the values sought to transform. One of the causes is that doesn’t have the motivation. In addition, the reasons that can be summarized from the results of the study regarding the lack of motivation are regulatory factors and the influence of the government; the distance between hospitals; the absence of rational legal order for transformation; financial readiness; unpreparedness of the hospitals, both administratively and financially; and the influence of parent companies.